The Struggle for Religious Ideologies in the Educational Institutions of Muhammadiyah and Nahdlatul Ulama: A Phenomenological Study in East Java - Dina Mardiana; Umiarso Umiarso; I’anatut Thoifah (Jurnal Madania)
This study focused on the phenomena or dynamics of the struggle for religious ideology that occur in the educational institutions (SMP/MTs and SMA/MA) of Muhammadiyah and Nahdlatul Ulama in East Java. Therefore, this study sought to see the internalization of the religious ideological values of Muhammadiyah and Nahdlatul Ulama in their education systems. Especially, when looking at clashes of religious thought that contain other ideologies (such as transnational (Salafi, Wahabi, and Shia), conservative/traditional, and reformist/modernist ideologies). This study used a qualitative approach and techniques for data collection used participatory observation, in-depth interviews, and documentation studies. The data analysis used the Miles, Huberman, and Saldana model consisting of four stages, namely, data collection, data condensation, data display, and conclusion. This study found that the educational institutions of Muhammadiyah and Nahdlatul Ulama have paradigmatic similarities, namely, ideology is positioned and functionalized as the motive and legitimacy of their educational actions and religious privileges. The expanding opportunities for dissemination and reproduction of other ideologies in their educational institutions are due to the very open nature of their religious understanding (Muhammadiyah has an understanding of Islamic Manhaji, and Nahdlatul Ulama has an understanding of Islamic Mahzabi).